Coefficient of tangential restitution for the linear dashpot model - Becker, Volker; Schwager, Thomas; Pöschel, Thorsten (Physical Review E, 2008)
The linear dashpot model for the inelastic normal force between colliding spheres leads to a constant coefficient of normal restitution, εn =const, which makes this model very popular for the investigation of dilute and moderately dense granular systems. For two frequently used models for the tangential interaction force we determine the coefficient of tangential restitution, εt, both analytically and by numerical integration of Newton's equation. Although εn =const for the linear-dashpot model, we obtain pronounced and characteristic dependences of the tangential coefficient on the impact velocity, εt = εt (g). The results may be used for event-driven simulations of granular systems of frictional particles. © 2008 The American Physical Society.